2004
DOI: 10.1038/sj.onc.1206981
|View full text |Cite
|
Sign up to set email alerts
|

H4(D10S170), a gene frequently rearranged with RET in papillary thyroid carcinomas: functional characterization

Abstract: Human thyroid papillary carcinomas are characterized by rearrangements of the RET protooncogene with a number of heterologous genes, which generate the RET/papillary thyroid carcinoma (PTC) oncogenes. One of the most frequent variants of these recombination events is the fusion of the intracellular kinase-encoding domain of RET to the first 101 amino acids of a gene named H4(D10S170). We have characterized the H4(D10S170) gene product, showing that it is a ubiquitously expressed 55 KDa nuclear and cytosolic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 33 publications
5
73
1
1
Order By: Relevance
“…Earlier work has shown that CCDC6 gene product is an ubiquitously expressed 65 kDa nuclear and cytosolic protein, is phosphorylated by extracellular signalregulated protein kinase after serum stimulation (Grieco et al, 1994;Celetti et al, 2004); it has also been proposed as a proapoptotic factor (Celetti et al, 2004). More recently, it has been shown that CCDC6 is involved in ATM-mediated cellular response to DNA damage, supporting the idea that the impairment of CCDC6 gene function might have a function in thyroid carcinogenesis (Merolla et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Earlier work has shown that CCDC6 gene product is an ubiquitously expressed 65 kDa nuclear and cytosolic protein, is phosphorylated by extracellular signalregulated protein kinase after serum stimulation (Grieco et al, 1994;Celetti et al, 2004); it has also been proposed as a proapoptotic factor (Celetti et al, 2004). More recently, it has been shown that CCDC6 is involved in ATM-mediated cellular response to DNA damage, supporting the idea that the impairment of CCDC6 gene function might have a function in thyroid carcinogenesis (Merolla et al, 2007).…”
Section: Introductionmentioning
confidence: 94%
“…The expression CCDC6 and mutant CCDC6 (1-101) plasmids and small-interfering RNAs (CCDC6i-345) have been described elsewhere (Celetti et al, 2004;Merolla et al, 2007). The expression plasmid pCMVSPORT6-CREB1 was from Invitrogen (Carlsbad, CA, USA).…”
Section: Expression Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…14,15 In previous work, we documented that CCDC6 (coiled-coildomain containing 6) acts as a proapoptotic protein substrate of ATM, to sustain DNA damage checkpoints in response to genotoxic events. 16,17 Moreover, CCDC6 protects genome integrity by modulating the activity of the phosphatase PP4C directed toward the dephosphorylation on S139 of the histone H2AX (gH2AX) in response to DNA damage. 18 Consistent with this, we reported that CCDC6 deficiency affects the gH2AX foci formation and the repair of the DNA DSBs.…”
mentioning
confidence: 99%
“…20 In most cancers that harbour the CCDC6 gene rearrangement, the product of the normal allele is either wholly absent or functionally impaired by a dominant negative mechanism. 16 Recently, CCDC6-RET fusions and CCDC6 inactivating mutations (N394Y, T462A, S351Y, E227K; www.sanger.ac.uk/genetics/ CGP/cosmic) have been reported in NSCLC. 21,22 In this study, we examined CCDC6 protein and mRNA levels in a group of NSCLC cell lines along with DNA repair proficiency, DNA damage response and platinum-based therapy as a single agent or in combination with PARP inhibitors.…”
mentioning
confidence: 99%